Prevalence of peri‐implantitis in a sample of HIV‐positive patients - Luca Casula; Andrea Poli; Tommaso Clemente; Giulia Artuso; Paolo Capparé; Enrico F. Gherlone (Wiley, 2021)
Abstract Objectives This study aimed to assess the prevalence of peri‐implantitis in human immunodeficiency virus (HIV)‐positive patients and the presence of a possible correlation between the immunological profile and serological values, of peri‐implantitis, and of possible differences between all‐on‐4 and single crown/bridge prostheses. Subjects and methods This retrospective study included 58 adult HIV‐positive patients (222 implants) with either all‐in‐4 prostheses or single crowns/bridges on at least one dental implant loaded for more than a year who were followed for 3 year (mean follow‐up). Data pertaining to the probing pocket depth (PPD), bleeding on probing, and immunological and systemic profile were collected. Results Patients with single crown/bridge implant rehabilitation showed higher prevalence of peri‐implantitis (34%) than patients with all‐on‐4 rehabilitation (0%) (p = 0.012). Patients with all‐on‐4 rehabilitation were significantly older than those with single crowns/bridges (p = 0.004). Patients with peri‐implantitis had implants for a significantly longer duration than those without (p = 0.001), implying that the probability of peri‐implantitis increases as the age of implant increases. Conclusions The prevalence of peri‐implantitis was 26% in the HIV‐positive patients population. No correlation was found between patients' immunological and serological factors and peri‐implantitis. The most important risk factor for peri‐implantitis and mucositis was implant age.